Effect of stainless steel meshes on the performance of passive micro direct methanol fuel cells - D. S. Falcão (2016)
An important issue related with Micro-DMFC is the two-phase flow that can occur on both sides of the cell. An efficient product removal is crucial to obtain higher performances, especially in passive Micro-DMFC. Passive devices do not need moving parts to feed oxidant and fuel to the cell, they use only natural convection/diffusion to fuel and oxidant supply without any additional power consumption, therefore the product removal is less efficient than in active ones. In the expectation of improving products removal from the cell, stainless steel meshes can be used between the membrane electrode assembly (MEA) and the current collectors. Several meshes with different characteristics are available in the market. In this work, different meshes are tested in a passive fuel cell with 2.25 cm(2) of active area at the anode and/or cathode sides looking for higher performances. Visualization studies at the anode side using a digital camera are also performed and constitute an important tool to observe carbon dioxide bubbles' profiles. The significantly higher performances obtained when using the meshes were explained by the combined effect of an enhanced current collection and a methanol crossover reduction leading to better distributed CO2 bubbles pattern. The best power output obtained was 29.3 mW/cm(2) using stainless steel meshes at both the anode and cathode sides, which is almost the double when comparing to the one obtained with the cell operating without mesh.